2013
DOI: 10.1007/s12281-013-0165-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage–Cryptococcus Interactions: An Update

Abstract: Cryptococcus species are fungal pathogens that are a leading cause of mortality. Initial inoculation is through the pulmonary route and, if disseminated, results in severe invasive infection including meningoencephalitis. Macrophages are the dominant phagocytic cell that interacts with Cryptococcus. Emerging theories suggest that Cryptococcus microevolution in macrophages is linked to survival and virulence within the host. In addition, Cryptococcus elaborates virulence factors as well as usurps host machinery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
(70 reference statements)
2
17
0
Order By: Relevance
“…To further determine the differences of humoral immune responses between LCG exposure group and HICG exposure group, we compared the proteome between the two groups directly. As shown in Figure 5A and Table S3, Here, we found that hemocytes failed to kill C. neoformans in G. mellonella, which is in line with previous reports that C. neoformans can evade macrophage attack 32,33 35 . These changes may help C. neoformans use these phagocytes as shelters for invasion and proliferation 32,33 .…”
Section: Glabrata Exposure Triggered the Proteome Changes Of G Mesupporting
confidence: 92%
“…To further determine the differences of humoral immune responses between LCG exposure group and HICG exposure group, we compared the proteome between the two groups directly. As shown in Figure 5A and Table S3, Here, we found that hemocytes failed to kill C. neoformans in G. mellonella, which is in line with previous reports that C. neoformans can evade macrophage attack 32,33 35 . These changes may help C. neoformans use these phagocytes as shelters for invasion and proliferation 32,33 .…”
Section: Glabrata Exposure Triggered the Proteome Changes Of G Mesupporting
confidence: 92%
“…Although no single pattern recognition receptor (PRR) has been shown to be required for binding of Cryptococcus , it is hypothesized that alveolar macrophages recognize Cryptococcus and initialize the immune response through multiple receptors such as Dectin-1, Mincle, mannose receptor, CD14, and toll-like receptors (TLRs) (Figure 1 .1) ( 27 30 ). The role of AMs and phagocytosis is believed to be critical during early infection, as observed in vivo imaging studies and animal models demonstrating enhanced susceptibility after AM depletion ( 31 , 32 ).…”
Section: Innate Recognitionmentioning
confidence: 99%
“…Some particles find their way into the alveolus where the resident cells of the innate immune system attempt to clear the infection. A large body of research shows an important role for alveolar macrophages in anti-cryptococcal defense by detecting and engulfing fungal spores (Giles et al, 2009; Mansour et al, 2014). Non-professional phagocytes, such as eosinophils and mast cells (MCs) have received less attention, although one report describes effector contribution of eosinophils and interaction of MCs and C. neoformans (Feldmesser et al, 1997).…”
Section: Introductionmentioning
confidence: 99%